Hydrodynamic modelling and reduction of irrigation releases from the Theewaterskloof dam to limit water loses - Saayman, Matthys Johannes (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--Stellenbosch University, 2012.